Effects of bedtime smartphone use on sleep quality among medical students: a cross-sectional study - Abdullah Sayed, M.; Sadikuzzaman, M.; Mahdi, Hasan Al; Bhattacharjee, Shatorupa; Mubin Uddin Akhanji, M.; Mia, Parvej (International Journal of Research in Medical Sciences, 2026)
Background: Sleep is essential for physical, mental, and cognitive health, especially among medical students facing academic pressure. However, bedtime smartphone use is increasingly disrupting sleep quality through blue light exposure and psychological stimulation. This leads to delayed sleep onset, reduced sleep duration, and daytime dysfunction. Despite growing concerns, limited research exists in this area among Bangladeshi medical students, making it important to explore the relationship between smartphone use and sleep quality. Objectives were to assess effects of bedtime smartphone use on sleep quality and its patterns among medical students. Methods: This cross-sectional study was conducted at a medical college in Sylhet Division from August to November 2025 among 100 medical students. Data were collected using a structured questionnaire covering smartphone use patterns and sleep quality (PSQI). Inclusion criteria included students aged 18-26 years using smartphones before sleep. Data were analyzed using SPSS v25, applying descriptive statistics and Chi-square test, with p<0.05 considered significant. Ethical approval and informed consent were obtained. Results: Among 100 participants, most were aged 21-23 years (46%), with a mean age of 22.4±2.1 years; 52% were male and 72% were MBBS students. Bedtime smartphone use was mainly 1-2 hours (38%), with social media as the most common purpose (42%, p<0.001). Poor sleep quality was observed in 68%, and 36% slept 5-6 hours. Higher smartphone use was associated with worse sleep outcomes and increased daytime sleepiness (78%). Conclusions: Bedtime smartphone use significantly disrupts sleep quality among medical students by affecting circadian rhythm and increasing cognitive stimulation.